A deep spectromorphological study of the γ -ray emission surrounding the young massive stellar cluster Westerlund 1 - Aharonian, F.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Becherini, Y.; Berge, D.; Bi, B.; Böttcher, Markus; De Lavergne, M. De Bony; Bradascio, F.; Brose, R.; Brun, F.; et al. (Astronomy & Astrophysics, 2022)
Context. Young massive stellar clusters are extreme environments and potentially provide the means for efficient particle acceleration. Indeed, they are increasingly considered as being responsible for a significant fraction of cosmic rays (CRs) that are accelerated within the Milky Way. Westerlund 1, the most massive known young stellar cluster in our Galaxy, is a prime candidate for studying this hypothesis. While the very-high-energy γ-ray source HESS J1646-458 has been detected in the vicinity of Westerlund 1 in the past, its association could not be firmly identified. Aims. We aim to identify the physical processes responsible for the γ-ray emission around Westerlund 1 and thus to understand the role of massive stellar clusters in the acceleration of Galactic CRs better. Methods. Using 164 h of data recorded with the High Energy Stereoscopic System (H.E.S.S.), we carried out a deep spectromorphological study of the γ-ray emission of HESS J1646-458. We furthermore employed H I and CO observations of the region to infer the presence of gas that could serve as target material for interactions of accelerated CRs. Results. We detected large-scale ( 2 diameter) γ-ray emission with a complex morphology, exhibiting a shell-like structure and showing no significant variation with γ-ray energy. The combined energy spectrum of the emission extends to several tens of TeV, and it is uniform across the entire source region. We did not find a clear correlation of the γ-ray emission with gas clouds as identified through H I and CO observations. Conclusions. We conclude that, of the known objects within the region, only Westerlund 1 can explain the majority of the γ-ray emission. Several CR acceleration sites and mechanisms are conceivable and discussed in detail. While it seems clear that Westerlund 1 acts as a powerful particle accelerator, no firm conclusions on the contribution of massive stellar clusters to the flux of Galactic CRs in general can be drawn at this point.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Acceleration of particles; Galaxies: star clusters: individual: Westerlund 1; Gamma rays: general; Radiation mechanisms: non-thermal; Shock waves; Stars: massive

Evidence for γ-ray emission from the remnant of Kepleras supernova based on deep H.E.S.S. observations - Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Böttcher, M.; Boisson, C.; et al. (Astronomy & Astrophysics, 2022)
Observations with imaging atmospheric Cherenkov telescopes (IACTs) have enhanced our knowledge of nearby supernova (SN) remnants with ages younger than 500 yr by establishing Cassiopeia A and the remnant of Tychoas SN as very-high-energy (VHE) ?-ray sources. The remnant of Kepleras SN, which is the product of the most recent naked-eye SN in our Galaxy, is comparable in age to the other two, but is significantly more distant. If the ?-ray luminosities of the remnants of Tychoas and Kepleras SNe are similar, then the latter is expected to be one of the faintest ?-ray sources within reach of the current generation IACT arrays. Here we report evidence at a statistical level of 4.6? for a VHE signal from the remnant of Kepleras SN based on deep observations by the High Energy Stereoscopic System (H.E.S.S.) with an exposure of 152 h. The measured integral flux above an energy of 226 GeV is ?0.3% of the flux of the Crab Nebula. The spectral energy distribution (SED) reveals a ?-ray emitting component connecting the VHE emission observed with H.E.S.S.To the emission observed at GeV energies with Fermi-LAT. The overall SED is similar to that of the remnant of Tychoas SN, possibly indicating the same nonthermal emission processes acting in both these young remnants of thermonuclear SNe.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Gamma rays: General; Ism: Supernova remnants; Radiation mechanisms: Non-Thermal; Supernovae: Individual: Kepler

Gammapy: A Python package for gamma-ray astronomy - Donath, Axel; Terrier, Régis; Remy, Quentin; Sinha, Atreyee; Nigro, Cosimo; Pintore, Fabio; Khélifi, Bruno; Olivera-Nieto, Laura; Ruiz, Jose Enrique; Brügge, Kai; Linhoff, Maximilian; Contreras, Jose Luis; et al. (Astronomy & Astrophysics, 2023)
Context. Traditionally, TeV-γ-ray astronomy has been conducted by experiments employing proprietary data and analysis software. However, the next generation of γ-ray instruments, such as the Cherenkov Telescope Array Observatory (CTAO), will be operated as open observatories. Alongside the data, they will also make the associated software tools available to a wider community. This necessity prompted the development of open, high-level, astronomical software customized for high-energy astrophysics. Aims. In this article, we present Gammapy, an open-source Python package for the analysis of astronomical γ-ray data, and illustrate the functionalities of its first long-term-support release, version 1.0. Built on the modern Python scientific ecosystem, Gammapy provides a uniform platform for reducing and modeling data from different γ-ray instruments for many analysis scenarios. Gammapy complies with several well-established data conventions in high-energy astrophysics, providing serialized data products that are interoperable with other software packages. Methods. Starting from event lists and instrument response functions, Gammapy provides functionalities to reduce these data by binning them in energy and sky coordinates. Several techniques for background estimation are implemented in the package to handle the residual hadronic background affecting γ-ray instruments. After the data are binned, the flux and morphology of one or more γ-ray sources can be estimated using Poisson maximum likelihood fitting and assuming a variety of spectral, temporal, and spatial models. Estimation of flux points, likelihood profiles, and light curves is also supported. Results. After describing the structure of the package, we show, using publicly available gamma-ray data, the capabilities of Gammapy in multiple traditional and novel γ-ray analysis scenarios, such as spectral and spectro-morphological modeling and estimations of a spectral energy distribution and a light curve. Its flexibility and its power are displayed in a final multi-instrument example, where datasets from different instruments, at different stages of data reduction, are simultaneously fitted with an astrophysical flux model.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Astroparticle physics; Gamma rays: general; Methods: data analysis; Methods: statistical

The KM3NeT potential for the next core-collapse supernova observation with neutrinos: KM3NeT Collaboration - Aiello, S.; Domi, Alba; Albert, A.; Garre, S. Alves; Aly, Z.; Ambrosone, A.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (European Physical Journal C: Particles and Fields, 2021)
The KM3NeT research infrastructure is under construction in the Mediterranean Sea. It consists of two water Cherenkov neutrino detectors, ARCA and ORCA, aimed at neutrino astrophysics and oscillation research, respectively. Instrumenting a large volume of sea water with ∼ 6200 optical modules comprising a total of ∼ 200 , 000 photomultiplier tubes, KM3NeT will achieve sensitivity to ∼10MeV neutrinos from Galactic and near-Galactic core-collapse supernovae through the observation of coincident hits in photomultipliers above the background. In this paper, the sensitivity of KM3NeT to a supernova explosion is estimated from detailed analyses of background data from the first KM3NeT detection units and simulations of the neutrino signal. The KM3NeT observational horizon (for a 5σ discovery) covers essentially the Milky-Way and for the most optimistic model, extends to the Small Magellanic Cloud (∼60kpc). Detailed studies of the time profile of the neutrino signal allow assessment of the KM3NeT capability to determine the arrival time of the neutrino burst with a few milliseconds precision for sources up to 5–8 kpc away, and detecting the peculiar signature of the standing accretion shock instability if the core-collapse supernova explosion happens closer than 3–5 kpc, depending on the progenitor mass. KM3NeT’s capability to measure the neutrino flux spectral parameters is also presented.
CRIS-Team Scopus Importer:2021-06-11

Time-resolved hadronic particle acceleration in the recurrent nova RS Ophiuchi - Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernloehr, K.; Bi, B.; et al. (Science, 2022)
Recurrent novae are repeating thermonuclear explosions in the outer layers of white dwarfs, due to the accretion of fresh material from a binary companion. The shock generated when ejected material slams into the companion star's wind can accelerate particles. We report very-high-energy [VHE: greater than or similar to 100 giga-electron volts] gamma rays from the recurrent nova RS Ophiuchi, up to 1 month after its 2021 outburst, observed using the High Energy Stereoscopic System (H.E.S.S.). The temporal profile of VHE emission is similar to that of lower-energy giga-electron volt emission, indicating a common origin, with a 2-day delay in peak flux. These observations constrain models of time-dependent particle energization, favoring a hadronic emission scenario over the leptonic alternative. Shocks in dense winds provide favorable environments for efficient acceleration of cosmic rays to very high energies.
CRIS-Team WoS Importer:2022-06-03

Unconventional conductivity increase in multilayer black phosphorus - Kolesnik-Gray, Maria; Meingast, Laura; Siebert, Martin; Unbehaun, Tim; Huf, Tobias; Ellrott, Günter; Abellan Saez, Gonzalo; Wild, Stefan; Lloret Segura, Vicente Josep; Mundloch, Udo; Schwarz, Julian; Niebauer, Michael; et al. (npj 2D Materials and Applications, 2023)
Multilayers of so-called 2D van der Waals materials have gained considerable attention as active components of next-generation electronic and optoelectronic technologies, with semiconducting black phosphorus (BP) regarded as one of the most promising systems. The applicability and performance limits of BP in both stand-alone and heterostructure-based multilayer devices are determined by individual flake charge transport properties, which synergistically depend on the number of layers and the strength of interlayer coupling between those. In this work, we study the DC electrical transport characteristics of high-quality BP field-effect devices within a wide range of flake thicknesses at room temperature. The experimental data show a non-trivial increase in conductivity and hole density with a reduced number of layers while maintaining constant field-effect mobility due to the prevalence of electron–phonon scattering. Based on the solution of the 1D Schrödinger–Poisson equation, we find that the observed phenomena are a direct consequence of non-negligible interlayer coupling, which in turn causes a local redistribution of free charge carriers towards the central layers. Our data show that due to the electrostatic conditions at the flake surfaces, a naturally protected 2D hole gas can be encapsulated in flakes as high as 10 nm, which preserves the bulk-like bandgap and effective carrier masses due to the electrostatic environment.
CRIS-Team Scopus Importer:2023-04-14